Young Elizabeth: Princess. Prisoner. Queen. By Nicola Tallis. London: Michael O’Mara Books, 2024. ISBN 978-1-78929-519-1. xxxiv + 398 pp. £25. - Johanna Strong (Royal Studies Journal)
Young Elizabeth: Princess. Prisoner. Queen. By Nicola Tallis. London: Michael O’Mara Books, 2024. ISBN 978-1-78929-519-1. xxxiv + 398 pp. £25.